Whole-Genome Sequencing Applied to the Molecular Epidemiology of Shiga Toxin-Producing Escherichia coli O157:H7 in Argentina - Masana, Marcelo Oscar; Carbonari, Claudia Carolina; Fittipaldi, Nahuel; Teatero, Sarah; Athey, Taryn B.T.; Pianciola, Luis; Melano, Roberto G.; Rivas, Marta; Chinen, Isabel (American Society for Microbiology, 2019)
Shiga toxin-producing Escherichia coli strains are worldwide associated with sporadic human infections and outbreaks. In this work, we report the availability of high-quality draft whole-genome sequences for 19 O157:H7 strains isolated in Argentina.